Scientific Structure Revolution, Epistemological Anarchism, and the Research Program in the New Philosophy of Science - Ramadhan Attalarik Iskandar; Sofyan Sauri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The philosophy of science should be able to educate generations of people in a country through education. This research includes three theories, namely: scientific structural revolution, epistemological anarchism, and research programs in the new philosophy of science. This new research on the philosophy of science from the ideas of Thomas Kuhn, Paul Feyerabend, and Imre Lakatos according to the specific scope of their theory can provide new contributions to the general public, because it contains concepts in the form of scientific structures, views of science, and renewable research programs that can be applied to the realm of education in the present by learning from experience based on basic wisdom and love, namely: (philosophy). It is hoped that this research can be used as a reference for future researchers to increase further understanding of the new philosophy of science that has been presented by the three philosophical ideas of science in efforts to develop education and can be utilized by all groups as well as possible according to the scientific domain, especially for teaching and future learners. nation for the sake of progress, regeneration, and education to become better.